2022
DOI: 10.3389/fvets.2022.877322
|View full text |Cite
|
Sign up to set email alerts
|

Video Endoscopy-Guided Intrabronchial Spray Inoculation of Mycobacterium bovis in Goats and Comparative Assessment of Lung Lesions With Various Imaging Methods

Abstract: Bovine tuberculosis (bTB) not only poses a zoonotic threat to humans but also has a significant economic impact on livestock production in many areas of the world. Effective vaccines for humans, livestock, and wildlife are highly desirable to control tuberculosis. Suitable large animal models are indispensable for meaningful assessment of vaccine candidates. Here, we describe the refinement of an animal model for bTB in goats. Intrabronchial inoculation procedure via video-guided endoscopy in anesthetized anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…To date, different approaches to MTBC experimental infections have been modelized in goats: transthoracic (Bezos et al, 2010 , 2015 ), endobronchial (Pérez de Val et al, 2011 ; Wedlich et al, 2022 ), aerosolization (Gonzalez-Juarrero et al, 2013 ), and the infection by contact approach, i.e., the exposure of susceptible goats to infected ones by close contact (Bezos et al, 2017 ; Roy et al, 2019 ). The latter has the advantage to mimic natural infection in the herd but has the disadvantage of not controlling critical points such as the infection time point, infection dose, and infection route, which hinder the monitorization of the infection progress and, most critically, comparison between treatment groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, different approaches to MTBC experimental infections have been modelized in goats: transthoracic (Bezos et al, 2010 , 2015 ), endobronchial (Pérez de Val et al, 2011 ; Wedlich et al, 2022 ), aerosolization (Gonzalez-Juarrero et al, 2013 ), and the infection by contact approach, i.e., the exposure of susceptible goats to infected ones by close contact (Bezos et al, 2017 ; Roy et al, 2019 ). The latter has the advantage to mimic natural infection in the herd but has the disadvantage of not controlling critical points such as the infection time point, infection dose, and infection route, which hinder the monitorization of the infection progress and, most critically, comparison between treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, cattle vaccination against TB is currently forbidden in the EU (Council Directive 78/52/EEC) due to interference with currently used TB diagnostic tools. The goat model of TB has proven to be a suitable one to study new TB vaccines for ruminants and humans and for a better understanding of the pathogenesis of the disease (Ramirez et al, 2003 ; Pérez de Val et al, 2011 , 2013 ; Wedlich et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, one report suggested that BCG has only a limited protective efficacy after challenge with M. caprae ( 259 ). More recent advanced goat models using video endoscopy for infection via intrabronchial spray inoculation ( 283 ) have demonstrated the relevance and suitability of goats for vaccine studies using BCG and new clinical candidates ( 284 , 285 ). Considering that BCG is the only licensed vaccine against TB it still remains the gold standard when testing new vaccine concepts.…”
Section: Large Animal Modelsmentioning
confidence: 99%
“…Goat TB closely resembles bovine and human TB in terms of immune response and pathological characteristics. They exhibit comparable patterns of disease progression, with a predominant anatomical localisation within the respiratory tract and the formation of caseous granulomas ( 77 , 107 ). In addition, goats demonstrate notable similarities in the anatomical structure of their respiratory tract, as well as a comparable size and body weight to that of humans ( 107 ).…”
Section: Comparative Pathology Of Animal Modelsmentioning
confidence: 99%
“…They exhibit comparable patterns of disease progression, with a predominant anatomical localisation within the respiratory tract and the formation of caseous granulomas ( 77 , 107 ). In addition, goats demonstrate notable similarities in the anatomical structure of their respiratory tract, as well as a comparable size and body weight to that of humans ( 107 ). These shared features present a unique opportunity to bridge the gap between murine preclinical studies and subsequent human investigations ( 77 , 105 ), thereby providing valuable insights into the intricate mechanisms of host-mycobacteria interaction ( 77 ).…”
Section: Comparative Pathology Of Animal Modelsmentioning
confidence: 99%